2015
DOI: 10.1007/s00704-015-1637-1
|View full text |Cite
|
Sign up to set email alerts
|

Detecting changes in surface water area of Lake Kyoga sub-basin using remotely sensed imagery in a changing climate

Abstract: Detection of changes in Earth surface features, for example lakes, is important for understanding the relationships between human and natural phenomena in order to manage better the increasingly scarce natural resources. This work presents a procedure of using Modified Normalised Difference Water Index (MNDWI) to detect fluctuations of Lake surface-water area and relate it to a changing climate. The study used radiometrically and geometrically rectified Landsat images for 1986, 1995 and 2010 encompassing the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Liou and Kar [18] conducted a review of evapotranspiration estimation with remote sensing and a number of surface energy balance algorithms. For the study area, Nsubuga et al [20] used remotely sensed Landsat images for 1986, 1995, and 2010 to detect changes in the surface water area of the LKB. Nsubuga et al [20] showed that the surface area of Lake Kyoga was increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Liou and Kar [18] conducted a review of evapotranspiration estimation with remote sensing and a number of surface energy balance algorithms. For the study area, Nsubuga et al [20] used remotely sensed Landsat images for 1986, 1995, and 2010 to detect changes in the surface water area of the LKB. Nsubuga et al [20] showed that the surface area of Lake Kyoga was increasing.…”
Section: Introductionmentioning
confidence: 99%
“…during the 2004/5 drought period, which correlated with Lake Victoria water levels dropping by a metre below the 10-year average (Kull, 2006). We have to remember that water resources are a proxy for climate variability (Nsubuga et al, 2015).…”
Section: Greenhouse Gas Emissionsmentioning
confidence: 99%
“…Considerable work has been done at a national level (Anyah and Semazzi, 2004;Osbahr et al, 2011;Nsubuga et al, 2011Nsubuga et al, , 2014aNsubuga et al, , 2014bNsubuga et al, , 2014cNsubuga et al, , 2015Bomuhangi et al, 2016), which has revealed various climatic changes in Uganda. The present work attempts to review various works in peer-reviewed articles and other forms of publication which have documented climate change in Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…Lake inundation can also trigger changes in chemical and morphometric characteristics such as the death of aquatic life and degradation of shoreline (Brito et al 2017). To the adjacent neighbourhoods, inundated areas might also instigate loss of property and lives (Nsubuga et al 2017;Tumusiime and Ageet 2018).…”
Section: Introductionmentioning
confidence: 99%